The Role of Participative Leadership, Time Management, and Customer Satisfaction on Service Performance in Indonesian Service Companies - Sofiyanti, Neneng (West Science Interdisciplinary Studies, 2025)
This study examines the role of participative leadership as a mediator between time management and customer satisfaction on service performance in Indonesian service companies. A quantitative analysis was conducted with a sample of 150 respondents, utilizing a Likert scale (1-5) and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results revealed that time management and customer satisfaction have significant direct positive effects on service performance, while participative leadership acts as a significant mediator in both relationships. Specifically, participative leadership enhances the impact of time management and customer satisfaction on service performance, suggesting its pivotal role in improving organizational outcomes. The findings emphasize the importance of cultivating participative leadership styles and optimizing time management practices and customer satisfaction strategies to enhance service performance in service-oriented industries. This study contributes to the literature on leadership, time management, and customer satisfaction in service performance contexts and offers practical implications for management practices in Indonesian service companies.